Striped Mealybug Ferrisia virgata Cockerell (Insecta: Hemiptera: Pseudococcidae) - Amanda Hodges (EDIS)
Includes: Introduction - Synonymy - Distribution - Description - Biology - Host Plants - Damage - Management - Selected References